CALCULATION OF CHEMICAL ATMOSPHERE ESTIMATION GIVEN THE COMPLEX TERRAIN - Biliaiev, M. M.; Mashihina, P. B. (Science and Transport Progress, 2010)
The 3D numerical model was used to simulate the toxic gas dispersion over a complex terrain after an accident spillage. The model is based on the K-gradient transport model and the model of potential flow. The results of numerical experiment are presented.